A possible case of glycogenic hepatopathy in a schoolboy with poorly controlled type 1 diabetes mellitus - A. Shalomi; K. Arulmoly (Sri Lanka College of Internal Medicine, 2024)
Glycogenic hepatopathy (GH) is a rare condition that can occur in individuals with poorly controlled diabetes mellitus, particularly in those with type 1 diabetes mellitus(T1DM). This condition is characterised by hepatomegaly and elevated liver enzymes. GH is associated with the accumulation of glycogen in the liver, which is a result of uncontrolled hyperglycemia and excessive glycogen storage in liver cells. We present a case of a 15-year-old boy who has been diagnosed with T1DM at the age of 8 and has experienced recurrent episodes of diabetic ketoacidosis (DKA). In this specific instance, he was admitted for treatment of DKA and was also diagnosed with GH.